Linking CD1-Restricted T Cells With Autoimmunity and Dyslipidemia: Lipid Levels Matter - Bagchi, Sreya; Genardi, Samantha; Wang, Chyung-Ru (Frontiers in Immunology, 2018)
Dyslipidemia, or altered blood lipid content, is a risk factor for developing cardiovascular disease. In addition, several autoimmune diseases, including systemic lupus erythematosus (SLE), psoriasis, diabetes, and rheumatoid arthritis, are correlated highly with dyslipidemia. One common thread between both autoimmune diseases and altered lipid levels is the presence of inflammation, suggesting that the immune system might act as the link between these related pathologies. Deciphering the role of innate and adaptive immune responses in autoimmune diseases and more recently, obesity related autoimmune inflammation, have been active areas of research. The broad picture suggests that antigen presenting molecules, which present self-peptides to autoreactive T cells, can result in either aggravation or amelioration of inflammation. However, very little is known about the role of self-lipid reactive T cells in dyslipidemia-associated autoimmune events. Given that a range of autoimmune diseases are linked to aberrant lipid profiles and a majority of lipid-specific T cells are reactive to self-antigens, it is important to examine the role of these T cells in dyslipidemia-related autoimmune ailments and determine if dysregulation of these T cells can be drivers of autoimmune conditions. CD1 molecules present lipids to T cells and are divided into two groups based on sequence homology. To date, most of the information available on lipid-reactive T cells comes from the study of group 2 CD1d-restricted natural killer T (NKT) cells while T cells reactive to group 1 CD1 molecules remain understudied, despite their higher abundance in humans compared to NKT cells. This review evaluates the mechanisms by which CD1-reactive, self-lipid specific T cells contribute to dyslipidemia-associated autoimmune disease progression or amelioration by examining available literature on NKT cells and highlighting recent progress made on the study of group 1 CD1-restricted T cells.